PENGARUH BOARD SIZE DAN BOARD LEADERSHIP TERHADAP NILAI PERUSAHAAN YANG TERDAFTAR DI JAKARTA ISLAMIC INDEX - Rinaldi, Dedy (Jurnal Ilmu Manajemen, 2016)
Formulation of the problem in this research is how the Influence of Board Size and Board Leadership to the Value of Registered Company on the Index Islamic Jakarta. The dependent variable (Y) in this study is the value of a company that is proxied through the Earning Per Share (EPS), return on assets (ROA), and Tobin's Q. Independent variable (X) consists of Board Size with indicator of the director number (X1), the number of commissioners (X2), the percentage of independent commissioners (X3), the audit committee (X4), and Board Leadership with indicator of managerial ownership (X5), and institutional ownership (X6), and variable control (C) used in this study is the size of the company and the company's debt.The population in this study is a registered company on the Index Islamic Jakarta > 5x from 2010-2014, thus, it acquired 20 companies as the simple random sampling technique. The required data are the company's financial reporting for each semester. The analytical method used is quantitative method by using multiple linear analysis.The results of the directors numbers (X1) and institutional ownership (X6) positive significantly influence to the value of the company. A variable number of commissioners (X2) negative significantly influence to the value of the company before any control variables, but a negative significant influence after any control variable on EPS and ROA. The percentage of independent commissioners (X3) consistently negative significant influence to the value of the company after the control variables, and only negative significant influence to Tobin's Q before any controls variable. Negative significant influences also found for Audit variable committee (X4) before and after the control variable of Managerial ownership (X5), therefore, the whole variables does not affect the value of the company, besides, negative significant influence can be seen on EPS before any control variables.